2009
DOI: 10.1128/jvi.00730-09
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Transmission of Human Immunodeficiency Virus Escape Mutations Subverts HLA-B57 Immunodominance but Facilitates Viral Control in the Haploidentical Infant

Abstract: Expression of HLA-B57 is associated with restricted replication of human immunodeficiency virus (HIV), but the mechanism for its protective effect remains unknown. If this advantage depends upon CD8 T-cell recognition of B57-restricted epitopes, mother-to-child transmission of escape mutations within these epitopes could nullify its protective effect. However, if the B57 advantage is largely mediated by selection for fitnessattenuating viral mutations within B57-restricted epitopes, such as T242N in TW10-Gag, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
48
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(54 citation statements)
references
References 38 publications
5
48
1
Order By: Relevance
“…Recent data have shown that transmission of HLA-B*57/B*5801 p24 Gag CD8 ϩ T-cell escape mutants to non-HLA-B*57/5801 individuals is associated with higher CD4 counts and contributes to a lower viral set point after acute infection in adults (6,14). In addition, similar advantage has been described in infants carrying B*57/B5801 escape HIV variants even in the absence of CD8 ϩ T-cell responses (40). Based on these findings, we investigated the relationship between the presence of mutations within HLA-B*57/5801-restricted p24 Gag CD8 ϩ T-cell epitopes and disease progression in our group of infants.…”
Section: Clinical Evolution and Virus Isolationmentioning
confidence: 71%
See 1 more Smart Citation
“…Recent data have shown that transmission of HLA-B*57/B*5801 p24 Gag CD8 ϩ T-cell escape mutants to non-HLA-B*57/5801 individuals is associated with higher CD4 counts and contributes to a lower viral set point after acute infection in adults (6,14). In addition, similar advantage has been described in infants carrying B*57/B5801 escape HIV variants even in the absence of CD8 ϩ T-cell responses (40). Based on these findings, we investigated the relationship between the presence of mutations within HLA-B*57/5801-restricted p24 Gag CD8 ϩ T-cell epitopes and disease progression in our group of infants.…”
Section: Clinical Evolution and Virus Isolationmentioning
confidence: 71%
“…HIV Gag CTL escape variants have been also associated with the control of viral replication after transmission to individuals lacking the restricting alleles (6,14). Moreover, presence of HLA-B*57 Gag escape variants have been show to be a relevant factor associated with HIV control in B*57 haploidentical infants, even in the absence of CD8 ϩ T-cell responses (40). We therefore evaluated the impact of mutations within HLA-B*57/ 5801-restricted epitopes in Gag and compensatory changes in the CypA binding loop associated with an increased RC.…”
Section: Discussionmentioning
confidence: 99%
“…Transmission of such isolates already harboring escape mutations may then potentially prevent early immune control. This was demonstrated for HIV-1, where compensated escape mutations were stable upon their transmission (43) and preexisting compensatory mutations facilitated the development of escape mutations associated with rapid disease progression even in the presence of protective HLA class I alleles (44). For HCV, it is unclear if the sequence of the transmitted virus also plays a role in subsequent immune control.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a recent study of children born to B57 ϩ mothers revealed reduced viral loads in the B57 ϩ children despite the transmission of B57 CTL escape mutants (54). In addition, there is a report of an inverse relationship between plasma viral load and the number of genotypic resistance mutations during primary infection (14).…”
Section: Discussionmentioning
confidence: 99%